2018
DOI: 10.3126/njog.v12i2.19959
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function test in abnormal uterine bleeding

Abstract: Aims: To evaluate and detect the thyroid dysfunction in patients with abnormal uterine bleeding (AUB) from puberty to menopause.Methods: This is an observational descriptive study of 90 patients of abnormal uterine bleeding at Paropakar Maternity and Women’s Hospital, Kathmandu from 17th January 2016 to 16th January 2017. Besides thyroid function test Pap smear, endometrial biopsy and histo-pathological examination of uterus following hysterectomy was done in selected cases.Results: The incidence of AUB was 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…The most common pattern of AUB was found to be menorrhagia was most common 45 (47.37%) followed by metrorrhagia 20 (21.05%), polymenorrhoea 13 (13.68%), menometrorrhagia 8 (8.42%), hypomenorrhoea 6 (6.31%), and oligomenorrhoea 3 (3.15%). This is similar to study done by Kattel, et al 4 where menorrhagia (36.7%) was most common complaint among AUB. Bhavani, et al 12 found the incidence of menorrhagia to be 54%.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most common pattern of AUB was found to be menorrhagia was most common 45 (47.37%) followed by metrorrhagia 20 (21.05%), polymenorrhoea 13 (13.68%), menometrorrhagia 8 (8.42%), hypomenorrhoea 6 (6.31%), and oligomenorrhoea 3 (3.15%). This is similar to study done by Kattel, et al 4 where menorrhagia (36.7%) was most common complaint among AUB. Bhavani, et al 12 found the incidence of menorrhagia to be 54%.…”
Section: Discussionsupporting
confidence: 92%
“…Oligomenorrhoea and hypomenorrhoea were associated with hyperthyroidism. This finding is similar to study done by Kattel, et al 4 Subedi, et al 11 and Byna, et al 17 TSH can be used as a screening test for every patient visiting gynaecology department with complaint of menstrual disorder. This will provide less financial burden to the patients rather than opting for whole thyroid function test.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most common type of abnormal uterine bleeding in this study was also menorrhagia followed by polymenorrhoea. In the study carried out by Kattel et al 23 thyroid dysfunction was present in 20% of abnormal uterine bleeding cases out of which 19% had hypothyroidism and 1% had hyperthyroidism. The most common type of abnormal uterine bleeding in this study was menorrhagia followed by metrorrhagia.…”
Section: Discussionmentioning
confidence: 91%